Using Question Generation and Mind Mapping Strategy toward Students’ Reading of Descriptive Texts - Atikah; Ikhsanudin; Dwi Riyanti (English Education:Journal of English Teaching and Research, 2024)
The purpose of this study was to find out the effect of a combination of question generation and mind mapping strategy toward reading comprehension of descriptive text. It was a quasi-experimental study at a private junior high school in Pontianak – Indonesia thatinvolved one control group and one experimental group. This applied cluster random to take the sample. The treatments were given four times. The data was collected through the reading comprehension test given to the control and experimental group. The data wereanalyzed with a t-test. It was to analyze the significance of the treatment. The research result showed that the t value isbigger than the ttable or t value > ttable. In short, the t value was 6.214 whilethe ttable was 1.9983, that the t value was biggerthan the ttable (6.214 > 1.9983) and the value of effect size was 1.49 meaning the combination between question generation and mind mapping strategy affected reading comprehension of descriptive text very strongly. Therefore, the combination of those strategies can be used to teach reading comprehension.